Impact of Ovarian Morphology on Endometrium Morphology, and Post Menopausal Bleeding - Madhu Chaturvedi; Khushboo S. Wadgaonkar (New Advances in Medicine and Medical Science Vol. 4, 2023)
This chapter evaluates and correlates presence of ovarian lesions with endometrial morphology in females presenting with post menopausal bleeding. Postmenopausal ovaries are chiefly composed of stroma and continue to have potential for hormonal synthesis. A total of 42 specimens of total abdominal hysterectomy with bilateral hysterectomy were investigated. The patients’ ages ranged from 45 to 80 years. The study did not discover any statistically significant correlation between high risk endometrial disease and stromal hyperplasia/large ovary.